Determination of HLA-A, -B and -DRB1 polymorphism in brain dead organ donors representative of the Colombian general population, 2007-2014 - Yazmin Rocío Arias; Karime Osorio-Arango; Brayan Bayona; Guadalupe Ercilla; Mauricio Beltrán-Durán (Biomédica, 2017)
Introduction: Genes encoding for human leukocyte antigens (HLA) are highly polymorphic and of great importance in organ transplantation procedures, as determining allelic frequencies in defined populations is taken into account among the scientific criteria for organ allocation. Objective: The objective of this study was to establish the antigen HLA-A, -B, and -DRB1 haplotype frequencies in organ donors representative of the Colombian population after brain death. Materials and methods: We conducted a descriptive retrospective study involving 2,506 cadaveric organ donors including an allelic and haplotype analysis of HLA-A, -B and -DRB1; we also determined the Hardy-Weinberg equilibrium. Results: We identified 21, 43 and 15 allelic loci for groups A*, B* and DRB1*, respectively. We detected 1,268 HLA-A, -B and -DR, 409 HLA-A-B, 383 HLA-DR-B, and 218 HLA-A-DR haplotypes. The three loci were found to be in Hardy-Weinberg equilibrium between the number of heterozygotes observed and the expected number, with p values of <0.05. Conclusions: This study provides information on the allelic distribution of HLA class I and II in organ donors from the six regions in which Colombia is structurally divided to provide transplant services.